PENGARUH PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BERAU - Kristian Bondon (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2022)
ABSTRACT The purpose of this study was to determine the effect of government spending (indirect spending and direct spending) on ​​economic growth in Berau District. The samples used in this study are the Berau District Government LRA time series for 2011-2020 and BPS Berau publication data in Figures for the 2012-2021 time series. The analytical tools used are: normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression analysis, correlation coefficient, coefficient of determination, t test, and F test. The results of the study concluded that: 1). Government spending through indirect spending has a partially significant effect on economic growth in Berau District. Evidenced by the results of the t test where t-count < - t-table (-4.383 < -2.365) and the significance value (Sig.) is smaller than the probability value (0.003 < 0.05); 2). Government spending through direct spending partially has a significant effect on economic growth in Berau District. Evidenced by the results of the t test where t-count > t-table (2.416 > 2.365) and the significance value (Sig.) is smaller than the probability value (0.046 <0.05); and 3). Government spending through indirect spending and direct spending has a significant simultaneous effect on economic growth in Berau District. This is evidenced by the results of the F test where F-count > F-table (10.139 > 4.74) and the significance value (Sig.) is smaller than the probability value (0.009 <0.05).